Antimicrobial Activity of Different Bark and Wood of Premna Serratifolia Lin - Rekha Rajendran, (International Journal of Pharma and Bio Sciences, 2010)
Premna serratifolia Lin., is an important medicinal herb (synonym- Premna integrifolia) known as “Munney” in Tamil, “Agnimantha” in Ayurveda and traditionally used for it’s as cardio tonic, antibiotic and antihyperglycemic properties. Plant has shown anticoagulant activity and the decoction of leaves exhibited anti-inflammatory and antiarthritic activity. However, its antimicrobial activity has not been investigated still now. Hence it was considered to evaluate the antimicrobial activity. The antimicrobial activity of different extracts of bark and wood of P.serratifolia Lin., was studied against nine bacterial and four fungal organisms by disc diffusion method. Ethylacetate, ethanol and aqueous extracts exhibited significant antibacterial activity, n-hexane and chloroform extracts exhibited moderate antibacterial activity and these five extracts exhibited significant antifungal activity. Results revealed that all the extracts possess a significant broad spectrum of antimicrobial activity when compared to Ciprofloxacin and Amphotericin-B may be due to the presence of phytoconstituents like alkaloids, irridoid glycosides and flavonoids present in it.